2000
DOI: 10.1111/j.1572-0241.2000.01851.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal gastric inflammatory infiltrates in inflammatory bowel diseases: prevalence, immunohistochemical characteristics, and diagnostic role

Abstract: Focal gastritis is relatively common in CD patients although it is not exclusive to this condition. Its recognition could be useful in the diagnostic workup of any patient with suspected or indeterminate inflammatory bowel disease, as it makes a diagnosis of CD more likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
21

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(76 citation statements)
references
References 18 publications
3
51
1
21
Order By: Relevance
“…In agreement with a recent, prospective study [8], in our series of CD patients, we identified microscopic inflammation in approximately 60% of cases. Hp is recognized as the most common cause of upper GI lesions, and Hp-related gastritis is characterized by increased numbers of acute and chronic inflammatory cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with a recent, prospective study [8], in our series of CD patients, we identified microscopic inflammation in approximately 60% of cases. Hp is recognized as the most common cause of upper GI lesions, and Hp-related gastritis is characterized by increased numbers of acute and chronic inflammatory cells.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, FAG was detected in approximately 30% of patients with a definite CD diagnosis, but was not used in any of the cases to establish the diagnosis of upper GI tract CD in the absence of macroscopic findings; indeed, FAG is not exclusive of CD [8][9][10][11]. Although in our series, all patients had an established diagnosis of CD and both macro and microscopical criteria were used to define upper CD involvement, the lack of a definite hallmark for an upper GI tract CD could represent a study limitation.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Previous studies have found that FEG had a prevalence of 46%-73% in Crohn's disease, suggesting FEG as a specifi c marker for Crohn's disease. [11][12][13][14] However, another report found that FEG was also commonly diagnosed (20.8%) in ulcerative colitis among children, which suggests that FEG is an indicator for infl ammatory bowel disease but does not differentiate Crohn's disease from ulcerative colitis. 25 Those fi ndings also triggered a study on FEG among a general adult patient population, which showed that FEG had a very low positive predictive value for infl ammatory bowel disease in a general population with a very low prevalence of infl ammatory bowel disease.…”
Section: Discussionmentioning
confidence: 91%
“…Sonderformen einer fokal betonten Gastritis oder Granulome sind zuweilen bei Patienten mit M. Crohn nachweisbar und kön-nen daher hilfreich sein in der Differenzialdiagnose zwischen Morbus Crohn und Colitis ulcerosa, bei Oberbauchbeschwerden oder unklarer Diarrhö [57,58].…”
Section: Erläuterungunclassified